Guiding Principles for the Conduct of Violence Study of Healthcare Workers and System (ViSHWaS): Insights from a Global Survey - Tanya Amal; Akshat Banga; Umme Habiba Faisal; Gaurang Bhatt; Aisha Khalid; Mohammed Amir Rais; Nadia Najam; Rahul Kashyap; Faisal A. Nawaz (University Library System, University of Pittsburgh, 2022)
• Background Globally many studies have reported on violence faced by healthcare workers. However, there is still a lack of homogeneous data to give us a concrete understanding of the present scenario on a global scale. Conducting a global survey required a robust team organization structure, unique dissemination strategies accounting for the regional limitations, and continual networking to maintain and propagate the pool of survey collaborators and responders. This study aims to describe the strategies that helped carry out a global survey- based study, the lessons learned, and recommendations for future studies.   • Methods This cross-sectional survey-based study was based on methodology of the "Hub and Spoke" model with the core team and sub-groups about different regions and managing country leads. The study was conducted across eight weeks from 6th June 2022 to 8th August 2022. The key steps included team organization, strategy formulation for survey dissemination and data collection, launching the project on social media, and conducting a post-survey amongst the collaborators. The Core Team convened weekly via video conference platforms to discuss the modus operandi, including the responsibilities of team members in communicating with HCWs from each country; strategies for data extraction and analysis. A standard message was created for the survey in English, which was spread via text, audio and video messages; the message was tailored according to the target region and population. The language barrier was managed by creating an audio translation or shifting to "an interviewer-administered" questionnaire. Call for leads and collaborators was organized through social media platforms and incentivized by proposing collaborative authorship   • Results A core team of 11 members from 7 countries was assembled, which expanded to 40 country leads from around 110 countries. We also amassed more than 75 regional collaborators who worked to provide feedback and spread the message. The "Violence Study of Healthcare Workers and Systems" (VISHWAS) amassed 5500 responses across the world. A weekly alternating trend in the number of survey responses was observed for eight weeks. Guiding principles garnered through this collaborative project include focusing on 1. Effective team organization, 2. Ensuring external validation of survey tool, 3. Personalized communication, 4. Global networking, 5. Timely communication for maintaining momentum, and 6. Addressing regional limitations. The post-survey analysis showed that WhatsApp messaging was the most common modality used for survey dissemination, followed by in-person meetings and text messaging. The successful techniques were noted to be 1. Direct communication with respondents, 2. Regular progress updates, 3. Responsiveness for regional and country lead's needs  4. Timely troubleshooting. The most common barriers for the respondents were limitations in language proficiency, technical fallouts, lack of compliance with, and difficulty understanding the questionnaire.   • Conclusion In this global survey-based study of more than 5500 responses from over 110 countries, valuable lessons in team management, survey dissemination, and addressing barriers to collaborative research. We thereby recommend incorporating the guiding principles from this study to design future surveys on a global scale.